2020
DOI: 10.3390/medicina56120688
|View full text |Cite
|
Sign up to set email alerts
|

From TELOCYTES to TELOCYTOPATHIES. Do Recently Described Interstitial Cells Play a Role in Female Idiopathic Infertility?

Abstract: The invention of such state-of-the art microscopic techniques like atomic force microscopy with a resolution of fractions of a nanometer, and the overall current level of knowledge in morphological disciplines have brought about a widespread impression, that identifying a new cell population in the 21st century is highly unlikely [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, the key conundrum that has to be resolved is the correlation vs. causality issue. This is relevant since functional aberrations or quantitative TC decrease are mentioned in majority of studies that explore the role of TCs in disease development (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, the key conundrum that has to be resolved is the correlation vs. causality issue. This is relevant since functional aberrations or quantitative TC decrease are mentioned in majority of studies that explore the role of TCs in disease development (14).…”
Section: Introductionmentioning
confidence: 99%
“…They can be identified by unique biomarker immunostaining and transmission electron microscopy scanning. Focusing on tumorigenesis, TCs were reported as an accelerative factor to promote the invasion and migration of cancer and cell proliferation (Klein et al, 2020). For instance, we demonstrated that when PDGF‐α stimulated TCs, the Raf/MEK/ERK signaling pathway was activated to increase MMP9 expression, which was a molecular mechanism by which TCs promote HCC metastasis (Xu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%